2015
DOI: 10.1016/j.asoc.2014.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Novel metaheuristic hybrid spiral-dynamic bacteria-chemotaxis algorithms for global optimisation

Abstract: This paper presents hybrid spiral-dynamic bacteria-chemotaxis algorithms for global optimisation and their application to control of a flexible manipulator system. Spiral dynamic algorithm (SDA) has faster convergence speed and good exploitation strategy. However, the incorporation of constant radius and angular displacement in its spiral model causes the exploration strategy to be less effective hence resulting in low accurate solution. Bacteria chemotaxis on the other hand, is the most prominent strategy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Some authors [8,9] had combined SDA with the bacterial foraging algorithm (BFA) to generate the optimal proportional-derivative controller of the flexible manipulator system, and the hybrid of SDA-BFA produced better control and higher accuracy than the original SDA. A similar hybrid algorithm was used for tuning the fuzzy-logic-control parameters of the flexible manipulator system [10,11]. These hybrid algorithms showed the best performance, achieving the highest accuracy while obtaining relatively faster convergence.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors [8,9] had combined SDA with the bacterial foraging algorithm (BFA) to generate the optimal proportional-derivative controller of the flexible manipulator system, and the hybrid of SDA-BFA produced better control and higher accuracy than the original SDA. A similar hybrid algorithm was used for tuning the fuzzy-logic-control parameters of the flexible manipulator system [10,11]. These hybrid algorithms showed the best performance, achieving the highest accuracy while obtaining relatively faster convergence.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, the bacterial chemotaxis (BC) heuristic simulated the movement of a single bacterium and evolutionary concepts to improve optimisation strategies and problem-solving capabilities. Since the development of BFO and BC, there has been a growing number of extensions that attempt to hybridise the algorithms with other metaheuristics and computational intelligence algorithms (e.g., [31,32,33,34,15]).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that the algorithm outperformed both BFA and SDA algorithms in terms of accuracy in finding a global optima solution. Compared to BFA, the total computation time has been significantly reduced and its convergence speed has been considerably increased [ 31 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 . The HSDBC algorithm has been tested to model and control nonlinear systems including flexible robot manipulator and a twin rotor system using a PD-like FLC [ 35 , 37 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation